Send Bygraves - Grimes, Martha frey50; Grebu, Devis (G.P. Putnam's Sons New York, 1989)
A spoof in verse of mystery fiction features a different style of poetry for every chapter.
Keywords: American Poetry; Detective and mystery stories -- Poetry